Application of spatial analytic hierarchy process in the selection of algal cultivation site for biofuel production: A case study in the Philippines - Ubando, Aristotle T. (Animo Repository, 2016)
Microalgae are considered as one of the promising advanced biomass feedstock for biofuel production offering higher oil yield per land area. The archipelagic nature of the Philippine and its tropical climate provide a thriving habitat for numerous microalgal species. The strategic deployment of algal cultivation sites in the country require a multi-criteria decision analysis based on available natural resources, social aspect, installed plants, and fuel demand per region. Hence, a spatial analytic hierarchy process was proposed to select potential cultivation regional sites in the Philippines. Due to the limiting attribute of the available natural resources and climactic type in each region, in this study, the available natural resources criterion was given more weight compared to other criteria. The results revealed that the preferred cultivation sites for the Philippines' group of islands were Region IV-A for Luzon, Region VII for Visayas, and Region XII for Mindanao. Future work includes the use of geographic information system coupled with analytic hierarchy process in identifying specific potential cultivation sites per region. © 2015 IEEE.